Inherited variant in NFκB‐1 promoter is associated with increased risk of IBD in an Algerian population and modulates SOX9 binding. Issue 3 (20th February 2020) - Hamadou, Imene; Garritano, Sonia; Romanel, Alessandro; Naimi, Dalila; Hammada, Talel; Demichelis, Francesca
Abstract: Background: The link between inflammation and cancer development was intensively studied in the last decade. To date, few studies explored the association between inflammatory genes and colorectal cancer (CRC) development. Aim: The present study aimed to evaluate the implication of three single nucleotide polymorphisms (SNPs), rs28362491 ins/del −94 ATTG in NFκB1, rs6920220 (G/A) in TNFAIP3, and rs419598 (C/T) in IL1RN, which play a role in inflammation regulation in CRC development. Methods and results: A case‐control study was conducted on an Algerian cohort of 358 subjects (147 healthy people, 89 individuals affected by inflammatory bowel disease [IBD], and 122 CRC patients enrolled at the University Hospital Center Ben Badis of Constantine). SNPs genotyping was performed by allelic discrimination TaqMan assay. The rs28362491 ins/del heterozygous genotype in NFκB1 conferred an increased risk of IBD compared with ins/ins homozygous genotype, with an increase of twofold (OR = 2.34 [1.29‐4.21]; 95% CI, 1.29‐4.21, P value = 0.004). No significant association was detected for the other two variants. Dual‐Luciferase Reporter Assay System performed in LoVo cells showed a significantly higher activity of the construct with ins allele of rs28362491 compared with the one harboring the del allele. Computational analysis nominated SOX9 as putative transcription factor (TF) with higher probability to bind the NFκB1 promoter at the SNP site, and we demonstrated in the in vitro assay that its overexpression modulates NFκB1 promoter activity in allele‐specific manner. Conclusion: We speculate that SOX9 may modulate the NFκB1 activity by binding its promoter at the SNP site in allelic specific manner.